A missão civilizatória dos direitos humanos: uma crítica da auto-alienação humana na era do capitalismo de desastre - Lucca Signorelli, Fernando de (2017)
This essay aims to answer the following questions: what are and how were human rights born? In order to answer these questions, we will first investigate how was born the concept of what is understood by human rights today. Next, we will research the history of the recent traditions of the rights, the Droit de l'homme et du citoyen and the rights of man, comparing them with the current human rights, to do so, we will use as a theoretical reference the Samuel Moyn’s work, an author who is a milestone in the historiography of human rights. In doing so, it will be seen that they are not the logical sequence of these ancient traditions of rights. With this, one can see that the history of human rights is not a linear history, much less a historical "trend". In the second part of the essay, after presenting a definition of human rights, we will address the efficacy of these rights. And we will take as theoretical reference Beth Simmons’s and Richard Posner’s works. These authors were chosen because Simmons represents the first great work with great investments of human and financial capital on the subject, and Posner's is the most recent work on the subject with the same qualities. In one way or another, both conclude their work by recognizing that human rights treaties did little or nothing to contribute to the development of people's well-being Finally, we will carry out an analysis of rights in capitalism, and then understand more deeply why human rights have today the "form" that they have. In doing so, it will be seen that human rights are a form of mercantile exchange relations at the international level.